2020
DOI: 10.1371/journal.pone.0239337
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of body age-based intervention in workplace health promotion: Results of a cohort study on 9851 Danish employees

Abstract: Introduction The aging population emphasize the need for effective health promotion interventions. The workplace is a prioritized setting for health promotion to reach widely within a population. Body age can be used as a health-risk estimate and as a motivational tool to change health behavior. In this study we investigate body age-based intervention including motivational interview and its effect on health, when applied to real life workplace health promotion. Material and methods Body age-based intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Thereby, a sleep-based AEE could improve health literacy 48 among patients. A recent Danish study found that interviews based on body age assessments motivates health promotion in the workplace, which lead to a decrease in smoking and metabolic syndrome among the employees 49 . Moreover, a meta-analysis found that health literacy was correlated with treatment adherence, especially among vulnerable groups 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, a sleep-based AEE could improve health literacy 48 among patients. A recent Danish study found that interviews based on body age assessments motivates health promotion in the workplace, which lead to a decrease in smoking and metabolic syndrome among the employees 49 . Moreover, a meta-analysis found that health literacy was correlated with treatment adherence, especially among vulnerable groups 50 .…”
Section: Discussionmentioning
confidence: 99%